COMPARISON OF ENGLISH PROFICIENCY IMPROVEMENT AMONG SELECTED FRESHMEN IN UNIVERSITAS ADVENT INDONESIA (UNAI) - Goodenough, Cherrilyne; Katemba`, Caroline V. (Journal of Language Pedagogy, 2011)
This study compared the improvement in English proficiency of freshmen who undertook the Remedial English and English I classes concurrently (Group A) with that of freshmen who had marginally better English proficiency scores and undertook the English I class only (Group B). The paired samples t-test on the gain scores resulted in a t-observed value of 2.604 at a significance level a = 0.05, thus the conclusion that Group A achieved better improvement in English language proficiency than Group B.